2015
DOI: 10.1080/10438599.2014.997460
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, location, and internationalization: empirical evidence for manufacturing SMEs

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 80 publications
0
16
0
1
Order By: Relevance
“…Additionally, as the accumulation, articulation, codification, and creation of knowledge are flexible in supporting dynamic capability development (Kogut and Zander 1992;Villar et al 2014), firms that utilize knowledge well can get better prepared for making changes and avoiding rigidities (Easterby-Smith and Prieto 2008). Moreover, knowledge can help firms perceive new business potentials and opportunities in response to environmental changes (Lejpras 2015).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Additionally, as the accumulation, articulation, codification, and creation of knowledge are flexible in supporting dynamic capability development (Kogut and Zander 1992;Villar et al 2014), firms that utilize knowledge well can get better prepared for making changes and avoiding rigidities (Easterby-Smith and Prieto 2008). Moreover, knowledge can help firms perceive new business potentials and opportunities in response to environmental changes (Lejpras 2015).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Studies on the efficiency of innovation activity among SMEs exist but they tend to have ambiguous findings: in some cases we can find a positive relationship (more innovation, more competitiveness) or a negative relationship (more innovation, less competitiveness) (e.g., Lewandowska & Stopa, 2019;Moen, 2018;Lejpras, 2015;Fitjar & Rodríguez-Pose, 2011;Petrov, 2011). We think that the positive or negative relationship depends on the type of an investment in innovation.…”
Section: Introductionmentioning
confidence: 99%
“…The research findings from Czechoslovakia obtained by Musteen and Datta (2011) revealed that SMEs' export performance is influenced directly and indirectly by product innovation capability. Meanwhile, a study of SMEs in Germany found that export propensity is associated with the output of innovation activities such as new product development and the number of patents (Lejpras, 2015). Another SME study conducted in Germany suggested that innovation capability and the adoption of information technology can enhance SMEs' likelihood of accessing the global market (Lecerf & Omrani, 2020).…”
Section: Product Innovation Knowledge and Smes' Internationalisationmentioning
confidence: 99%